Comparative Analysis of Repeatability of Manual and Automated Choroidal Thickness Measurements in Nonneovascular Age-Related Macular Degeneration - Lee, Sieun; Fallah, Nader; Forooghian, Farzin; Ko, Ashley; Pakzad-Vaezi, Kaivon; Merkur, Andrew B.; Kirker, Andrew W.; Albiani, David A.; Young, Mei; Sarunic, Marinko V.; Beg, Mirza Faisal (Investigative ophthalmology & visual science, 2013)
We compared the reproducibility and mutual agreement of the subfoveal choroidal thickness measurements by expert raters and an automated algorithm in enhanced depth imaging optical coherence tomography (EDI-OCT) images of eyes with nonneovascular age-related macular degeneration (AMD). We recruited 44 patients with nonneovascular AMD and EDI-OCT images were acquired. Subfoveal choroidal thickness was measured manually by two expert raters and automatically by a graph-cut-based algorithm. Drusen area was measured using the automated software (version 6) of Cirrus SD-OCT. The manual and automated choroidal thickness measurements were compared in reproducibility, mutual agreement, and correlation with drusen area. The mean subfoveal choroidal thickness was 246 ± 63 μm for the first rater, 214 ± 68 for the second rater, and 209 ± 53 for the automated algorithm. Intraclass correlation coefficients (ICC) and 95% confidence intervals (CI) were 0.96 (CI 0.94-0.98) between the raters, 0.85 (CI 0.77-0.90) between the first rater and the automated algorithm, and 0.84 (CI 0.75-0.89) between the second rater and the automated algorithm. Repeat scan measurement ICCs were 0.91 (CI 0.86-0.94) for the first rater, 0.96 (CI 0.94-0.97) for the second rater, and 0.87 (CI 0.80-0.92) for the automated algorithm. Manual and automated measurements were correlated with drusen area. The automated algorithm generally yielded smaller choroidal thickness than the raters with a moderate level of agreement. However, its repeat scan measurement repeatability was comparable to that of the manual measurements. The mean difference between the raters indicated possible biases in different raters and rating sessions. The correlation of the automated measurements with the drusen area was comparable to that of the manual measurements. Automated subfoveal choroidal thickness measurement has potential use in clinical practice and clinical trials, with possibility for reduced time and labor cost.